2020
DOI: 10.1002/smll.202001440
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Graphdiyne and Graphdiyne Oxide

Abstract: From manufacture to disposal, the interaction of graphdiyne based nanomaterials with living organisms is inevitable and crucial. However, the cytotoxic properties of this novel carbon nanomaterial are rarely investigated, and the mechanisms behind their cytotoxicity are totally unknown. In this study, the antibacterial activity of graphdiyne (GDY) and graphdiyne oxide (GDYO) is reported. GDY is capable of inhibiting broad‐spectrum bacterial growth while exerting moderate cytotoxicity on mammalian cells. In com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 68 publications
1
68
0
Order By: Relevance
“…118 It was also found that cellular membranes of bacteria could be pierced by the extremely sharp edges of graphdyine nanosheets, causing the leakage of intracellular substances. 119 The antibacterial activity of graphdyine was higher in comparison to graphene and GO. Therefore, potential similar antiviral effects can be expected for graphdiyne and possibly Ti3C2Tx MXene and also for other 2DMs with high flexibility, stiffness, and strains.…”
Section: Future Possibilities For Functionalization Of 2dms Against Virusesmentioning
confidence: 96%
“…118 It was also found that cellular membranes of bacteria could be pierced by the extremely sharp edges of graphdyine nanosheets, causing the leakage of intracellular substances. 119 The antibacterial activity of graphdyine was higher in comparison to graphene and GO. Therefore, potential similar antiviral effects can be expected for graphdiyne and possibly Ti3C2Tx MXene and also for other 2DMs with high flexibility, stiffness, and strains.…”
Section: Future Possibilities For Functionalization Of 2dms Against Virusesmentioning
confidence: 96%
“…Zhu et al [107] studied the bacterial toxicity of GDY and GDYO, and further explored the antibacterial mechanism of GDY. The investigation of the antibacterial behaviors of GDY based nanomaterials may provide useful guidelines for the future design and application of this novel molecular allotrope of carbon [107] .…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Similar to the destructive effect of graphene on bacterial pathogen membrane [141,142] , GDY can also induce the collapse of bacterial cell membrane by capturing or wrapping bacterial cell membrane. Zhu et al [107] observed the formation of GDY and bacteria aggregation in bacterial culture. With the extension of culture time, the bacterial cell had no deformation, meaning that wrapping bacterial membrane was a possible way to inhibit bacterial growth.…”
Section: Physical/mechanical Punctuationmentioning
confidence: 99%
See 2 more Smart Citations